2012
DOI: 10.1007/s10461-012-0286-y
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Discordance Between Biologic and Self-Reported Measures of Semen Exposure: A Qualitative Study Among Female Patients Attending an STI Clinic in Jamaica

Abstract: Correspondence to: Marion W. Carter, acq0@cdc.gov. HHS Public Access Author Manuscript Author ManuscriptAuthor Manuscript Author ManuscriptWe explored the use of qualitative interviews to discuss discrepancies between two sources of information on unprotected sex: biomarker results and self-reported survey data. The study context was a randomized trial in Kingston, Jamaica examining the effect of STI counseling messages on recent sexual behavior using prostate-specific antigen (PSA) as the primary study outco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 32 publications
0
8
0
Order By: Relevance
“…As previously revealed in a qualitative study conducted among a subset of the participants informed about their PSA positivity (following rapid testing at follow up), this social desirability bias may have prevented women from reporting failure to adhere to clinic staff’s instructions. 11 In contrast, at enrollment, women were asked to report on their behaviors, including unprotected sex, before any counseling messages were provided. Whether misreporting would have regressed to baseline levels (from participants becoming desensitized to counseling messages) or would have increased (from effect of cumulative messages) had our trial been longer is unknown.…”
mentioning
confidence: 99%
“…As previously revealed in a qualitative study conducted among a subset of the participants informed about their PSA positivity (following rapid testing at follow up), this social desirability bias may have prevented women from reporting failure to adhere to clinic staff’s instructions. 11 In contrast, at enrollment, women were asked to report on their behaviors, including unprotected sex, before any counseling messages were provided. Whether misreporting would have regressed to baseline levels (from participants becoming desensitized to counseling messages) or would have increased (from effect of cumulative messages) had our trial been longer is unknown.…”
mentioning
confidence: 99%
“…Misreport of UVS among women living with HIV/AIDS hampers efforts to decrease sexual transmission of HIV by masking the intervention effects of condom promotion interventions and interfering with the interpretation of study findings related to condom use. Similar to the work conducted by the VOICE study team [20] and work with PSA among women in Jamaica [21], our results would benefit from follow-up qualitative interviews to uncover the reasons for misreported unprotected sex, and to determine correlates of misreport. Continued research on sexual risk behavior should incorporate semen biomarkers such as PSA as an adjunct to self-reported condom use.…”
Section: Discussionmentioning
confidence: 82%
“…27 In addition to reporting bias, sometimes participants are unaware of their exposure. 15,22 Participants in clinical trials evaluating barrier methods of contraception, for example, may not be aware of some exposures such as a condom slippage or breakage that results in small exposures to semen. 22,27 By contrast, some participants may report that they had an exposure or experienced issues with the condom, when the use of biomarkers yields negative results for semen exposure.…”
Section: General Considerations For Determining the Need For Semen Bimentioning
confidence: 99%
“…8-23 Yc-DNA has also been used in studies evaluating self-reported condom use of adolescents. 10 PSA has been used to validate self-reports of recent sexual activity, 10-20 including among female participants receiving treatment for STIs advised to avoid sex (or unprotected sex), 14-15 and as an indicator of condom nonuse or failure. 4-11,14,15,21 …”
Section: Introductionmentioning
confidence: 99%